STUDY ON SELECTION PARAMETERS AND INTERASSOCIATIONS OF YIELD, AGRONOMIC TRAITS AND CANOPY TEMPERATURE IN RELATION TO DROUGHT TOLERANCE IN WHEAT - J. M.PATEL; S. K. PATEL; C. R. PATEL; D. R. CHAUDHARI (The Bioscan, 2020)
Twenty genotypes of wheat revealed highly significant differences for all the characters studied, indicating the presence of substantial genetic variability in the material screened under drought condition. The phenotypic and genotypic coefficient of variation (PCV and GCV) was moderate for grain yield, spike length, thousand grain weight, grain weight per spike, number of spikelets per spike and number of tillers per meter. High heritability along with high genetic advance as percent of mean was observed for grain yield, spike length, number of spikelets per spike and thousand grain weight might ultimately be considered as a tool for effective selection of drought tolerant genotypes. Results also revealed strong positive genotypic associations for grain yield with number of tillers per meter (0.951), whereas moderate to low association with grain weight per spike (0.220) and plant height (0.196) was observed. Under drought stress condition canopy temperature (-0.271) correlated negatively with grain yield also suggested the importance of cooler genotypes for drought stress condition. The interrelationship among these traits studied revealed that grain yield could be efficiently improved by obtaining maximum expression of tillers per meter followed by plant height, grain weight per spike and lower canopy temperature under drought conditions.